Bioinformatic Analyses and Experimental Verification Reveal that High FSTL3 Expression Promotes EMT via Fibronectin-1/α5β1 Interaction in Colorectal Cancer - Liu, Yuanjie; Li, Jiepin; Zeng, Shuhong; Zhang, Ying; Zhang, Yonghua; Jin, Zhichao; Liu, Shenlin; Zou, Xi (Frontiers in Molecular Biosciences, 2021)
Background: Colorectal cancer (CRC) is typical cancer prevalent worldwide. Despite the conventional treatments, CRC has a poor prognosis due to relapse and metastasis. Moreover, there is a dearth of sensitive biomarkers for predicting prognosis in CRC. Methods: This study used a bioinformatics approach combining validation experiments to examine the value of follistatin-like 3 (FSTL3) as a prognostic predictor and therapeutic target in CRC. Results: FSTL3 was remarkably upregulated in the CRC samples. FSTL3 overexpression was significantly associated with a poor prognosis. FSTL3 was found to activate the epithelial-mesenchymal transition by promoting the binding of FN1 to α5β1. FSTL3 expression was also positively correlated with the abundance of the potent immunosuppressors, M2 macrophages, Conclusion: FSTL3 overexpression affects CRC prognosis and thus, FSTL3 can be a prognostic biomarker and therapeutic target with potential applications in CRC.